The mechanism of Girdin in degenerative brain disease caused by high glucose stimulation - Liu, Longteng; Zhang, Jinsong; Han, Yanxi; Liu, Dongge (Frontiers in Endocrinology, 2022)
Girdin, as an actin binding protein, plays a major role in maintaining the stability of the actin skeleton structure, and affects the growth, development, and migration of neurons. This article discusses the mechanism of Girdin in brain degeneration caused by high glucose stimulation. We tested the expression of Girdin in diabetic patients. The positive expression rate of Girdin in the diabetic group was 17.2% (5/29), which was obviously lower than the positive expression rate of 83.3% (20/24) in the non-diabetic group. The expression of Girdin and its signaling pathway related proteins Akt and STAT3 in hippocampal neurons under high glucose stimulation. The results showed that contrast to the control group (glucose concentration 25 mmol/L), the expression of Girdin in the high-glucose group (glucose concentration 225 mmol/L) was reduced (P < 0.05); the phosphorylation levels of Akt and STAT3 related to Girdin signaling pathway were also reduced (P < 0.05). Under high-glucose stimulation, the structure of neurons is abnormal, synapses become shorter, the number of synaptic branches decreases, and dendritic spines decrease or disappear; the number of neurons decreases, and there is apoptosis. In addition, Girdin and P-Akt are less expressed in neurons and synapses, especially the most obvious reduction in synaptic ends. The activity of Girdin and its signaling pathway related proteins Akt and STAT3 decreased in neurons under high glucose stimulation, indicating that the mechanism of Girdin in brain degeneration caused by high glucose stimulation is closely related to Akt and STAT3 pathways.